2016
DOI: 10.1134/s1021443716020126
|View full text |Cite
|
Sign up to set email alerts
|

Pigments and photosynthesis of understory grasses: Light irradiance and soil moisture effects

Abstract: Phleum alpinum L. and Poa pratensis L. are major forage species that often grow in various environments in Tierra del Fuego, Argentina. We performed a greenhouse experiment to investigate how these species acclimate to the different irradiance of the microenvironments where they grow. Both grass species were exposed to three levels of incident irradiance (I4: 4%; I26: 26%, or I64: 64% of ambient sunlight) and two levels of soil moisture content (M30: 30-50% or M60: 60-80% of field capacity) under greenhouse co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Physiological alterations induced by PPT in plants expressing the bar gene still remain unclear [46]. Chlorophylls and carotenoids are the main components of the photosynthetic apparatus, and change in their content could provide information on the physiological state of leaves [47]. Chlorophyll content [7] and fluorescence [48] are among well-known signs in assessing plants' damage after stress treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological alterations induced by PPT in plants expressing the bar gene still remain unclear [46]. Chlorophylls and carotenoids are the main components of the photosynthetic apparatus, and change in their content could provide information on the physiological state of leaves [47]. Chlorophyll content [7] and fluorescence [48] are among well-known signs in assessing plants' damage after stress treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moisture is an important factor affecting the photosynthetic, physiological characteristics of plants [22]. Soil moisture affects crop photosynthetic rate [23]. The amount of irrigation and mulching will affect soil moisture content, affecting the water absorption of crops, and ultimately impacting the photosynthesis of crops.…”
Section: Effect Of Irrigation Amount On P N and T R Of Degradable Filmentioning
confidence: 99%
“…The literature shows several studies conducted on chlorophyll content suggesting that by monitoring and evaluating chlorophyll content in tree leaves and plants, their responses to environmental stressors, weather and climatic conditions, as well as anthropogenic conditions can be inferred [6]. Chlorophyll content has been shown to be a reliable factor for evaluating plant-life processes and their resistance to stressful conditions such as humidity and temperature changes [7]. One study showed that the decline in chlorophyll content is very fast when plants are in high stress condition and very similar to the changes in pigment during leaf senescence [8].…”
Section: Introductionmentioning
confidence: 99%